2009
DOI: 10.1029/2008jd011230
|View full text |Cite
|
Sign up to set email alerts
|

Validation of MODIS Terra, AIRS, NCEP/DOE AMIP‐II Reanalysis‐2, and AERONET Sun photometer derived integrated precipitable water vapor using ground‐based GPS receivers over India

Abstract: [1] Water vapor is an important and highly variable constituent in time and space; the knowledge of its variability is important in climate studies. In India, the ground observations of water vapor using conventional methods such as radiosonde are limited. In this paper, a comparison of hourly estimates of total column water vapor from Global Positioning System (GPS) with multisensor satellite is presented over three stations. We show quantitatively seasonal and monthly dependency of bias, standard deviation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
75
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(86 citation statements)
references
References 50 publications
10
75
0
1
Order By: Relevance
“…This variation of the bias as a function of the IWV value has also already been described in the literature (e.g. Ohtani and Naito, 2000;Deblonde et al, 2005;Prasad and Singh, 2009;Vey et al, 2010), but alternative explanations were formulated. For instance, Ohtani and Naito (2000) considered the effects of the seasonal variation of the GPS mapping function as one of the causes for their observed annual variation of the GPS-RS biases.…”
Section: Summary For the Nh Intercomparisonsupporting
confidence: 73%
“…This variation of the bias as a function of the IWV value has also already been described in the literature (e.g. Ohtani and Naito, 2000;Deblonde et al, 2005;Prasad and Singh, 2009;Vey et al, 2010), but alternative explanations were formulated. For instance, Ohtani and Naito (2000) considered the effects of the seasonal variation of the GPS mapping function as one of the causes for their observed annual variation of the GPS-RS biases.…”
Section: Summary For the Nh Intercomparisonsupporting
confidence: 73%
“…It is because the AIRS observation values depend on the observation locations and seasons and the PWV derivation algorithms are different from each other (Raja et al 2008). Prasad & Singh (2009) reported that GPS results observed in India and the AIRS results showed the seasonal bias error about 1-4 mm and the root mean square error of 3-8 mm.…”
Section: Comparative Verification Of the Trendmentioning
confidence: 99%
“…Over the IG plains, the monsoon rainfall starts in July, which not only washes out the aerosols in the atmosphere (low aerosol loading), but also increases water vapor content in the atmosphere (Prasad and Singh, 2009;Prasad et al, 2007). The aerosol concentration is lowest over IG plains during July-August due to heavy monsoon rainfall and that leads to negligible cooling or heating trend (TMT) (Fig.…”
Section: Role Of Aerosols and Greenhouse Gasesmentioning
confidence: 99%